A Review Study on Psychological Disorders in Youth of India - Ghanshyam Vatsa, (AG Volumes, 2022)
Adolescence is the earliest age at which symptoms of mental health problems in adults first appear. This phrase, at first glance, appears to make the obvious point that, in order to comprehend adult mental illness, we must first comprehend the events that occurred before to adulthood. If this is the case, then the years between infancy and adolescence, which are separated by the rite of passage known as puberty, are of critical importance for unravelling the roots of adult disease. This would provide the basis for primary and secondary preventive initiatives. In keeping with the overall topic of this supplement, this study examines the similarities between the teen and early adult years and argues that they should be seen together as a single developmental period. There is also some allusion to infancy since the roots of many problems that show at this time were already planted at an earlier age.